Smoking in adolescence as a predictor of early loss of periodontal attachment - Hashim R, Thomson WM, Pack ARC (Blackwell Synergy, 2001)
On the basis of information from studies of older adults, smoking is considered to be an important risk factor for periodontal disease. Examining periodontal loss of attachment among younger adults means a lower contribution from cumulative exposure to other environmental risk factors.